Wise chair 2009 - Domen Zupančič (AR: Arhitektura, Raziskave, 2012)
Paper furniture design is not a novelty; at our school, too, students have designed objects and even a dome made from paper. What is new is that our colleagues created useful elements and presented them to the most demanding users - children. Having seen the response and spirited understanding of the children, I was very happy about this collaboration between the university and the nursery.